Achievement of capitation indicators based on Performance (kbk) bpjs at puskesmas makroman Samarinda - Dwi Listiyani; Ratno Adrianto; Irfansyah Baharuddin Pakki (Mulawarman International Conference on Tropical Public Health, 2025)
Background: The National Health Insurance Program (JKN) applies Performance-Based Capitation (KBK) to improve efficiency and service quality at primary health facilities. Makroman Health Center, however, has not consistently met key indicators—contact rate, controlled Prolanis participants, and non-specialistic referral ratios—affecting both service quality and capitation funding. Evidence on KBK implementation in semi-urban primary care settings remains limited.ObjectiveTo describe the achievement of the three KBK indicators—contact rate, controlled Prolanis participant ratio, and non-specialistic referral ratio—and analyze their implications for capitation payments at Makroman Health Center, Samarinda, during 2022–2024. Research Methods / Implementation Methods : This descriptive observational study used secondary quantitative data from BPJS Health and the P-Care application. Variables included the three KBK indicators and corresponding capitation fund adjustments. Data were collected through document review and analyzed descriptively to identify annual trends and performance achievements across the study period. Results : Performance achievement varied over the three years. The contact rate rose from 45.02‰ in 2022 to 77.21‰ in 2024 but remained far below the KBK target of 150‰, indicating limited service accessibility. The non-specialistic referral ratio consistently met the <2% target in 2023–2024, showing improved primary care case management. However, the proportion of controlled Prolanis participants remained below the minimum 5% target throughout the period, reflecting ongoing challenges in chronic disease management. As a result, capitation payment adjustments ranged only from 85% to 90% of the expected amount. These findings demonstrate progress in referral control but persistent gaps in accessibility and chronic care continuity. Conclusion / Lesson Learned : KBK implementation at Makroman Health Center has not yet reached optimal performance. While referral quality has improved, low contact rates and poor Prolanis control continue to reduce capitation payments. Strengthening outreach activities, data quality monitoring, and structured Prolanis programs is essential for improving service performance and maximizing the effectiveness of KBK as a performance-based financing mechanism.